Does Financial Distress Have An Impact On Stock Price? - Santi Octaviani; Nikke Yusnita Mahardini; Nana Umdiana (Universitas Serang Raya, 2024)
Abstract This study aims to determine the effect of Financial Distress using the Altman Z-Score forming variables; WCTA, RETA, EBITTA, MVEBVL and STA on Stock Price and to determine the effect of WCTA, RETA, EBITTA, MVEBVL, STA on Stock Price. This research was conducted using quantitative methods. The population of this study amounted to 17 companies in the Metal Sub-Sector Manufacturing Company listed on the Indonesia Stock Exchange for the 2016-2020 period and a sample of 11 companies was taken using purposive sampling method. The data analysis method uses Altman Z-Score and multiple linear regression analysis and is processed with SPSS version 25. Based on the results of the analysis, it can be concluded that the variables RETA, EBITTA, STA have no effect on Stock Price and the variables WCTA, and MVEBVL affect Stock Price. And together the Altman Z-Score variables affect the Stock Price. Keywords: Altman Z-Score, WCTA, RETA, EBITTA, MVEBVL, STA and Stock Price.